Redefining Entry-Level Analyst Roles in M&A: Essential Skillsets in the Age of AI-Powered Diligence - Shounik, Shaurya (Emerging Frontiers Library for The American Journal of Applied Sciences, 2025)
The mergers and acquisitions field within investment banking is changing because artificial intelligence tools like natural language processing and machine learning are now part of everyday work. Historically, entry-level analysts performed extensive data-driven analyses crucial for executing transactions, but this role has been significantly influenced by the introduction of AI. This study explored how AI has altered the duties and skill requirements for junior analysts in M&A environments. A qualitative content analysis framework was used to synthesize insights from over 50 reports, journal articles, case studies, and industry surveys published between 2020 and 2025. Data were collected from reputable sources, including global consulting firms, academic journals, and financial services publications. Through an in-depth literature review, new critical skills were identified. These encompassed advanced data analysis, proficient prompt engineering, and thorough validation of AI models. The results highlighted a need for analytical flexibility, technological expertise, and adaptability among analysts entering the industry. As a result, investment banking firms focused on M&A were compelled to update training programs and redefine analyst responsibilities. Adopting these skills helped facilitate a smoother shift into technology-enhanced workflows, ultimately allowing analysts to contribute greater strategic value towards transaction processes. But there are still obstacles to overcome, especially when it comes to relying too much on AI and not having enough human supervision to avoid algorithmic mistakes. Looking outward, we see that analysts are turning into AI-enabled specialists, combining their knowledge with digital abilities to improve deal outcomes.